BENTUK DAN MAKNA PENAMAAN NAMA PADI DI KECAMATAN TANGARAN KABUPATEN SAMBAS - Verawati Verawati; Patriantoro Patriantoro; Agus Syahrani (Universitas Tanjungpura, 2022)
This research uses a qualitative descriptive method. The source of the data for this research is the native speaker of the Sambas Malay language whose work is rice farmers and understands the concept of rice. The data obtained are in the form of words or phrases of the names of rice in Tangaran District, Sambas Regency, the lexical meaning of each rice variety, and the cultural meaning of rice naming. The data obtained in this study contained 62 data on types of rice in Tangaran District, Sambas Regency, with word forms totaling 17 data consisting of monomorphemic noun categories, phrase forms totaling 45 total data in noun categories, lexical meanings there were 62 data describing the physical condition of each type of rice, cultural meaning, there are 23 data that describe the cultural meaning contained in this type of rice. This research is associated with learning Indonesian for Class VII SMP in semester 1 of the 2013 curriculum which is used as teaching material for descriptive texts. There are 2 descriptive texts designed as teacher reviews, the texts are about rice pulut dade ruan and rice kak canting .